B-CELL SUBPOPULATIONS OF PERIPHERAL BLOOD IN SYSTEMIC LUPUS ERYTHEMATOSUS - A. I. Budkova; S. V. Lapin; M. K. Serebriakova; I. V. Kudryavtsev; I. N. Trishina; A. L. Maslyansky; A. A. Totolian (Медицинская иммунология, 2017)
Distinct changes of B-cell subpopulations are observed in most systemic rheumatic diseases associated with polyclonal B cell hyperreactivity. Immunosuppressive and cytostatic therapy may also differentially influence B lymphocyte subsets in these. We studied subpopulations of B cells in systemic rheumatic patients along treatment with cytostatics. We analyzed B cell phenotypes in ninety-nine blood samples from the patients with systemic lupus erythematosus (SLE, n = 25), systemic sclerosis (n = 27), Sjogren’s syndrome (n = 47) in the course of their hospital treatment. Control group consisted of 49 healthy blood donors. Phenotyping of blood B-cell subpopulations was performed by means of flow cytometry (Beckman Coulter, USA). Naïve B-cell subpopulations in SLE patients who underwent cyclophosphan treatment, were underrepresented, if compared with normal control group, whereas plasmablast levels were increased irrespectively of medication mode. B cell population exhibits a natural heterogeneity, thus making it necessary to analyze distinct B cell subpopulations as independent functional units, when studying different rheumatic diseases. The levels of plasmablasts which are active antibody producers, remain high, despite immunosuppressive therapy performed in SLE. Thus, therapy targeted against certain B cell subsets, could be able to provide a more effective treatment for the patients with systemic rheumatic diseases.